Steroid withdrawal improves blood pressure control and nocturnal dipping in pediatric renal transplant recipients: analysis of a prospective, randomized, controlled trial - Höcker, Britta; Fichtner, Alexander; Wühl, Elke; Tönshoff, Burkhard (Pediatric nephrology, 2019)
BackgroundVariable effects of steroid minimization strategies on blood pressure in pediatric renal transplant recipients have been reported, but data on the effect of steroid withdrawal on ambulatory blood pressure and circadian blood pressure rhythm have not been published so far.MethodsIn a prospective, randomized, multicenter study on steroid withdrawal in pediatric renal transplant recipients (n = 42) on cyclosporine, mycophenolate mofetil, and methylprednisolone, we performed a substudy in 28 patients, aged 11.2 ± 3.8 years, for whom ambulatory blood pressure monitoring (ABPM) data were available.ResultsIn the steroid-withdrawal group, the percentage of patients with arterial hypertension, defined as systolic and/or diastolic blood pressure values recorded by ABPM > 1.64 SDS and/or antihypertensive medication, at month 15 was significantly lower (35.7%, p = 0.002) than in controls (92.9%). The need of antihypertensive medication dropped significantly by 61.2% (p < 0.000 vs. control), while in controls, it even rose by 69.3%. One year after steroid withdrawal, no patient exhibited hypertensive blood pressure values above the 95th percentile, compared to 35.7% at baseline (p = 0.014) and to 14.3% of control (p = 0.142). The beneficial impact of steroid withdrawal was especially pronounced for nocturnal blood pressure, leading to a recovered circadian rhythm in 71.4% of patients vs. 14.3% at baseline (p = 0.002), while the percentage of controls with an abnormal circadian rhythm (35.7%) did not change.ConclusionsSteroid withdrawal in pediatric renal transplant recipients with well-preserved allograft function is associated with less arterial hypertension recorded by ABPM and recovery of circadian blood pressure rhythm by restoration of nocturnal blood pressure dipping.